Dose and time dependence of box jellyfish antivenom - Athena Andreosso; Michael J Smout; Jamie E Seymour (Journal of Venomous Animals and Toxins including Tropical Diseases, 2014)
Background The effectiveness of the currently available box jellyfish (Chironex fleckeri) antivenom has been subject of debate for many years. To assess whether the box jellyfish antivenom has the ability to attenuate venom-induced damage at cellular level, the present study analyzed the dose and time dependence of the antivenom in a cell-based assay. Methods Different doses of antivenom were added to venom and subsequently administered to cells and the cell index was measured using xCelligence Technology (ACEA Biosciences). Similarly, antivenom and venom were incubated over different time periods and cell survival measured as stated above. For both experiments, the cell index was plotted as a measure of cell survival against the dose or incubation time and significance was determined with the use of a one-way ANOVA with a LSD post hoc test. Results Increasing concentrations of antivenom significantly augmented cell survival, with a concentration of approximately five times the currently recommended dose for human envenomation, causing the first significant increase in cell survival compared venom alone. Further, cell survival improved with increasing incubation time of venom and antivenom prior to addition to the cells, indicating that box jellyfish antivenom requires approximately 70 minutes to neutralize C. fleckeri venom. Conclusion The presented results suggest that the currently recommended dose of antivenom requires adjustment, and more importantly, a human trial to test the effects of higher concentrations is also necessary. Further, antivenom has delayed neutralizing effects (i.e. after 70 minutes) which underlines the eminence of immediate and prolonged cardiopulmonary resuscitation in victims suffering from a C. fleckeri venom-induced cardiovascular collapse.